Hubungan Pengetahuan dengan Kepatuhan Perawat dalam Menerapkan Pencegahan Risiko Jatuh di Ruang Rawat Inap RSI Sultan Agung Banjarbaru - Velia Nur Fauziah; Muh Abdurrouf; Retno Issroviatiningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explains the analysis of the relationship between nurses' knowledge and compliance in implementing fall risk prevention in the inpatient ward of RSI Sultan Agung Banjarbaru. Fall risk is one of the most common patient safety incidents in hospitals, with significant impacts on the physical, psychological, and financial conditions of patients. Data from RSI Sultan Agung Banjarbaru in 2024 recorded three fall incidents, while a preliminary survey showed that 40% of nurses had insufficient knowledge of fall risk prevention and 60% were not compliant with existing preventive procedures. This study aims to determine the relationship between nurses' knowledge and compliance in reducing patient fall risk. The study design used a quantitative approach with a cross-sectional method, involving 97 nurses selected through simple random sampling. The instruments used were questionnaires designed to measure nurses' knowledge and compliance. Data were analyzed using Somers’ D test. The results showed that the majority of nurses had good knowledge (87.6%) and high compliance (90.7%). Additionally, a very strong and significant relationship was found between nurses' knowledge and compliance in implementing fall risk prevention (Somers’ D = 0.844; p = 0.000). This indicates that good knowledge of fall risk prevention procedures is strongly related to nurses' compliance in applying preventive measures. Therefore, it is essential for hospitals to provide ongoing education and training to enhance patient safety. With improved knowledge and compliance among nurses, fall risks are expected to be minimized, and patient safety can be better maintained.